Challenging the U.S.-led war on drugs: Argentina in comparative perspective - Cutrona, Sebastián Antonino (Routledge studies in Latin American politics, 2017)
Introduction: the U.S. counter-narcotics strategy in the Americas -- The emergence and consolidation of the standard security model: exploring the Colombian case -- 1983-1989: the Alfonsín administration -- 1989-1999: the Menem administration -- 1999-2015: the Kirchners' administrations -- The drug-problem today -- Conclusions: lessons from deviance -- Epilogue: the Macri administration